Incidencia de los indicadores de logro en la construcción de los reactivos de base estructurada en el área de estudios sociales, para los docentes de la Escuela “Loja” de la parroquia Eloy Alfaro, cantón Latacunga en el año lectivo 2014-2015 - Caillagua Suntasig, Jessica Mariana (2015)
The genralobjetive of this researching was to ―investigate the different theories that have to the incidence of performance indicators in the builiding base reactive social área for teachers in Basical Education School‖ Loja‖. This work is a response to the problem that is the incidence of performance indicators structured based reagents in the Social área? The methods used were: historical, deductive, inductive and analytic-synthetic; Historical researching in background; deductive in performing categories and variables; inductive to obtaineg conclusions on field researching in analytic and synthetic analysis and interpretation of data. The findings are in curriculum planning are not considered essential evaluation indicators; skills with performance criteria unrelated to the essential evaluation indicators. The evaluation techniques tools are not considers with the nature of indicators of achievement and teachers do not have to taxonomic level of the ítems. The contribution is of designed a manual developing learning strategics in evaluation tools that help in the teaching learning process.